1997
DOI: 10.1128/jb.179.20.6318-6324.1997
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two heat shock genes from Haloferax volcanii: a model system for transcription regulation in the Archaea

Abstract: The expression of two heat-responsive cct (chaperonin-containing Tcp-1) genes from the archaeon Haloferax volcanii was investigated at the transcription level. The cct1 and cct2 genes, which encode proteins of 560 and 557 amino acids, respectively, were identified on cosmid clones of an H. volcanii genomic library and subsequently sequenced. The deduced amino acid sequences of these genes exhibited a high degree of similarity to other archaeal and eucaryal cct family members. Expression of the cct genes was ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 60 publications
(71 reference statements)
2
54
0
1
Order By: Relevance
“…It has been reported that both the a-and the b-subunits of chaperonin accumulate in response to a high growth temperature and/or heat shock in archaea such as S. shibatae (Trent et al, 1991;Kagawa et al, 1995), P. occultum (Phipps et al, 1991), Haloferax volcanii (Kuo et al, 1997) and Archaeoglobus fulgidus (Emmerhoff et al, 1998). The ratio of the a-to b-subunit is constant at different growth temperatures, and their expression is thought to be co-regulated (Phipps et al, 1991;Trent et al, 1991;Kagawa et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that both the a-and the b-subunits of chaperonin accumulate in response to a high growth temperature and/or heat shock in archaea such as S. shibatae (Trent et al, 1991;Kagawa et al, 1995), P. occultum (Phipps et al, 1991), Haloferax volcanii (Kuo et al, 1997) and Archaeoglobus fulgidus (Emmerhoff et al, 1998). The ratio of the a-to b-subunit is constant at different growth temperatures, and their expression is thought to be co-regulated (Phipps et al, 1991;Trent et al, 1991;Kagawa et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the hypothesis that the bsubunit is adapted to a higher temperature than the asubunit. The a-subunit may be the prototype from which the b-subunit has evolved, because it has the GGM repeat sequence that is conserved in group I chaperonin (McLennan et al, 1993;Brocchieri and Karlin, 2000) and in some chaperonins of archaea belonging to Euryarchaeota (Kuo et al, 1997;Yoshida et al, 1997;Furutani et al, 1998). The a-subunit might have been lost after the divergence of the Pyrococcus species from the Thermococcus species.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, at the present time, regulation of archaeal transcription initiation and mRNA stability have been addressed mostly in methanogens and halophiles, representatives of the Euryarchaeota, but very little information is available on extreme-and hyperthermophilic archaea. Moreover, though mobility shift experiments performed with archaeal protein extracts and analyses of cisacting regulatory elements (11,13,21,22,24,31,39,46,48,52,53) have indicated the existence of sequence-specific DNAbinding proteins and of target sites located close to the transcription initiation sites of specific genes, these potential regulatory elements have not been characterized thoroughly (for a recent review, see reference 33). Only one detailed study has been performed (2) (see Discussion).…”
mentioning
confidence: 99%
“…This suggests that under moderate salt deprivation, a first level of response consists in minimizing the loss of ions. Interestingly, in halophilic strains, many of the genes encoding for thermal stress response proteins are also induced under low salt conditions, thus confirming that low salt represents a physico-chemical stressor (68). We studied the accumulation of specific proteins in H. marismortui and H. salinarum cells exposed to prolonged low salt stress conditions, similar to the one we used for neutrons experiments.…”
Section: Cellular Responses To Fluctuating Salt Environmentsmentioning
confidence: 73%
“…We specifically searched for large complexes in the hydrophobic fractions of the total cytosolic extracts of H. salinarum and H. marismortui. These studies revealed that the type II chaperonin complex, called "thermosome" in archaea, is strongly accumulated within cells exposed to low salt conditions (68)(69)(70). Gene expression studies indicated that the heat shock promoter of the thermosome is also strongly salt regulated, suggesting that the low salt and the heat and salt stressors use similar, if not identical, transcriptional regulators.…”
Section: Cellular Responses To Fluctuating Salt Environmentsmentioning
confidence: 99%